Financial Frictions and Business Cycles in Middle-Income Countries - Guajardo, Jaime (IMF Working Papers; Working Paper, 2008)
A standard DSGE small open economy model can not generate the cyclical regularities of middle-income countries. It predicts excessive consumption smoothing, and procyclical, instead of countercyclical, real net exports. Previous studies have solved this problem by increasing the shocks' persistence or by lowering the intertemporal elasticity of substitution. This paper tackles the problem by introducing market imperfections relevant for MICs into an otherwise standard model. More specifically, I build a model with limited access to the foreign capital market, identified as an external borrowing constraint, and asymmetric financing opportunities across nontradable and tradable sectors, identified as a sector-specific labor financing wedge. The key parameters associated to these frictions are deduced to replicate selected data for Chile between 1986 and 2004. I find that both frictions are necessary to replicate the cyclical regularities of middle-income countries as they help the model reproduce different features of the data: The external borrowing constraint makes investment and consumption of tradable goods more procyclical and volatile, and makes real net exports countercyclical, while the sector-specific labor financing wedge makes the model reproduce the cyclical moments of work hours and consumption of non tradable goods.